A preliminary study of strategic competitiveness of MDF industry in Peninsular Malaysia by using SWOT analysis - Othman, Mohd Shahwahid; Abdul Samad, Abdul Rahim (Canadian Center of Science and Education, 2009)
Within three decades, the medium density fibreboard (MDF) industry has grown and contributed significantly to the external trade of the wood-based sector of Malaysia. Today the industry is at a cross road. Although, trade is expanding, but initial relative advantages over other competitors have marginally eroded. Over time new critical success factors played important roles as the industry responded to changes in global challenges. Through an industrial survey using the strength, weakness, opportunity and threat (SWOT) approach, this paper assesses only these four elements as a preliminary study for further analysis in analysing the strategic competitiveness and core competencies of MDF industry.